Examining the Role of Customer Engagement in Mediating the Effect of Product Knowledge on Purchase Intention in E-Commerce - Firdaus; M. Roby Jatmiko; Jumai; Martini; Wa Ode Sitti Nurrahmah; Sri Sulistiyaningsih; Meizar Effendi (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
:  The rapid growth of e-commerce has intensified competition, encouraging businesses to better understand the factors influencing consumers’ purchase intention. Product knowledge is considered a crucial determinant, not only affecting purchase intention directly but also through customer engagement on digital platforms. This study aims to examine the role of customer engagement in mediating the effect of product knowledge on purchase intention in the e-commerce context. A quantitative approach was employed using a survey method involving 250 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that product knowledge has a positive and significant effect on customer engagement and purchase intention. Customer engagement also exerts a strong and significant influence on purchase intention. However, the interaction effect reveals that customer engagement does not significantly mediate the relationship between product knowledge and purchase intention. The R-square values demonstrate that the model explains a substantial proportion of variance in purchase intention. These findings highlight the importance of enhancing product knowledge and effectively managing customer engagement as key strategies for improving consumers’ purchase intention in e-commerce marketing.